Testing numerical reliability of data analysis systems - Sawitzki, Günther (Computational statistics & data analysis, 1994)
We discuss some typical problems of statistical computing, and testing strategies for the testing data analysis systems. For one particular area, regression, we illustrate these problems and strategies.